The complete Brecht toolkit - Unwin, Stephen; Jones, Julian (Nick Hern Books, 2016)
"Examines, one by one, Brecht's many, sometimes contradictory ideas about theatre - and how he put them into practice. Here are explanations of all the famous key terms, such as Alienation Effect, Epic Theatre and Gestus, as well as the many others which go to make up what we think of as 'Brechtian theatre'. There follows a section which looks at the practical application of these theories in Acting, Language, Music, Design and Direction."--P. [4] of cover.